Young Investigators Award Session - ASMIHA Indonesian Heart Association (The Indonesian Heart Association, 2020)
Abstracts of the 29th Annual Scientific Meeting of the Indonesian Heart Association (ASMIHA) 1st ASMIHA Digital Conference, 23-25 October 2020